Pengembangan Aplikasi Standar Keperawatan Pada Asuhan Keperawatan Anak Di RSUD Indramayu - Bachtiar Efendi; Winani Winani; Adi Suheryadi (Universitas Persada Indonesia YAI, 2023)
The Regional General Hospital (RSUD) Indramayu has not implemented the Hospital ManagementInformation System optimally, and also for nursing diagnoses, nursing outcomes, nursinginterventions according to nursing standards have not been included in the system. So that thecommunication and documentation of nursing care that is carried out is still different between fellownurses. In 2021, community service has been held in the form of Application of Standard NursingCare for Medical Surgical Nursing Care at Indramayu Hospital and with this applicationcommunication and documentation of medical surgical nursing care are uniform. So that theIndramayu Hospital asked the Indramayu State Polytechnic to continue community service at theIndramayu Hospital in the pediatric nursing section. The method of implementing communityservice consists of several stages, including: identification of problems and needs, analysis andplanning, system creation, testing and evaluation, and reporting the results of the implementationof service. This community service partnering with RSUD Indramayu produces android-basedapplications and web-based applications and is centered on the server. This application containsthree standard nursing books, namely SDKI, SLKI and SIKI. This application also links the SDKIbook with the SLKI book and links the SDKI book with the SIKI book. The conclusion of communityservice regarding the development of making the application of pediatric nursing standards is the realization of the development of standard nursing applications consisting of an android platformand a website platform, so that the communication of child nursing care becomes uniform.Recording and documentation of uniform pediatric nursing care